Colony attendance and at‐sea distribution of thin‐billed prions during the early breeding season. (10th April 2014) - Quillfeldt, Petra; Phillips, Richard A.; Marx, Melanie; Masello, Juan F.
<x xml:space="preserve">Abstract</x> Procellariiform seabirds have extreme life histories; they are very long‐lived, first breed when relatively old, lay single egg clutches, both incubation and chick‐rearing are prolonged and chicks exhibit slow growth. The early part of the breeding season is crucial, when pair bonds are re‐established and partners coordinate their breeding duties, but is a difficult period to study in burrow‐nesting species. Miniature geolocators (Global Location Sensors or GLS loggers) now offer a way to collect data on burrow attendance, as well as determine at‐sea movements. We studied the early breeding season in thin‐billed prions Pachyptila belcheri breeding at New Island, Falkland Islands. Males and females arrived back at the colony at similar times, with peak arrival in the last days of September. However, males spent more time on land during the pre‐laying period, presumably defending and maintaining the burrow and maximising mating opportunities. Males departed later than females, and carried out a significantly shorter pre‐laying exodus. Males took on the first long incubation shift, whereas females returned to sea soon after egg laying. During the pre‐laying exodus and incubation, males and females travelled at similar speeds (> 250 km d−1) and were widely distributed over large areas of the Patagonian Shelf. Inter‐annual differences in oceanographic conditions were stronger during the incubation than during the pre‐laying exodus and were matched by stronger differences in distribution. The study thus suggests that extended trips and flexible distribution enable thin‐billed prions to meet the high energy demands of egg production and incubation despite low productivity in waters around the colony during the early summer.